Compendium of key documents relating to human rights and HIV in Eastern and Southern Africa - Edited by AIDS and Human Rights Research Unit, a collaboration between the Centre for the Study of AIDS and the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2008)
Compendium of key documents relating to human rights and HIV in Eastern and Southern Africa Edited by AIDS and Human Rights Research Unit, a collaboration between the Centre for the Study of AIDS and the Centre for Human Rights, University of Pretoria 2008 ISBN: 978-0-9802658-9-7 Pages: xi 313 Print version: Available Electronic version: Free PDF available